Programa de ensino informatizado e individualizado do alfabeto digital por equivalência de estímulos. - Carvalho, Dariel de (2005)
ABSTRACT This study had as objective, develops, implements and evaluates an informatized and individualized teaching program to qualify deaf students in the application of digital alphabet. For that, two studies were conducted with 12 deaf children, with ages between seven and twelve years that were studying in an institution of support to deaf people in a city in São Paulo state. In Study 1 was evaluated the skills related to digital alphabet through selection tasks and construction tasks. The stimulus was pictures and words represented in digital alphabet or in Arabic alphabet. The results showed many individual variations, with some students presenting some degree of coherence in all the evaluated relations, while others presented low percentages of coherence and just for some of the relations; however, most of them presented difficulties in the task to name a picture (composing name, selecting letter to letter, in the correct sequence, in any of the alphabets). The 12 participants were then exposed to the Study 2 that consisted of application and evaluation of a teaching program. The teaching tasks consisted of selecting a word of the digital alphabet when the picture was the model, select and sequence letters of the digital alphabet to construct a word like the one in the model and select a word in Arabic alphabet, when the word in the digital alphabet was the model. The others relations were potentially emergent, according to the predictions of the equivalence paradigm and were simply tested. It as used two subject delineating as its own control to evaluate the efficiency of the program, one of pre and post test and one of multiple base line in words. There were five teaching steps in the program; in each step three words were taught (two other words, composed by syllable recombination of the teaching words were just evaluated, for generalization). It was also evaluated an execution task in which in front of the model (picture, pressed word in digital alphabet or pressed word in the Arabic alphabet) the participant was supposed to express the gesture movement of the digital alphabet (spelling). Nine of the twelve participants concluded the program and presented better performances in the post-test comparing to the pre-test. The teaching fortified relations that was still not well established and favored the establishing of some skills that were not presented in the background before the beginning of the program. The data of multiple base line showed the changes in naming the pictures (in any of the alphabets) just after the teaching of a relation between picture and the pressed word related and this happened in a systematic way, for the 15 words, for most of the participants. This delineation also showed maintenance of the acquired background, for most of the words and most of the participants that concluded the program. The discussion focused the importance of the teaching and the potential benefits of the domain of the skills evolved in the use of digital alphabet by the deaf students.